Running world cross-country championships: A unique model for pacing (International Journal of Sports Physiology and Performance, 2014)
The aim of this study was to describe the pacing distribution during 6 editions of the world cross-country championships. Methods: Data from the 768 male runners participating from 2007 to 2013 were considered for this study. Blocks of 10 participants according to final position (eg, 1st to 10th, 11 to 20th, etc) were considered. Results: Taking data from all editions together, the effect of years was found to be significant (F5,266 = 3078.69, P < .001, w2 = 0.31), as well as the effect of blocks of runners by final position (F4,266 = 957.62, P < .001, w2 = 0.08). A significant general decrease in speed by lap was also found (F5,1330 = 2344.02, P < .001, w2 = 0.29). Post hoc analyses were conducted for every edition where several pacing patterns were found. All correlations between the lap times and the total time were significant. However, each lap might show different predicting capacity over the individual outcome. Discussion: Top athletes seem to display different strategies, which allow them to sustain an optimal speed and/or kick as needed during the critical moments and succeed. After the first group (block) of runners, subsequent blocks always displayed a positive pacing pattern (fast to slow speed). Consequently, a much more stable pacing pattern should be considered to maximize final position. Conclusions: Top-10 finishers in the world cross-country championships tend to display a more even pace than the rest of the finishers, whose general behavior shows a positive (fast-to-slow) pattern.